The Relationship of Body Mass Index with Length of Stay in Symptomatic Cholelithiasis Patients Who Have Undergoing Open Cholecystectomy at RSUS Lippo Village Karawaci Hospital - Alvionitan, Chellya Fanny; Sudirman, Taufik (Medicinus, 2025)
Background: Gallstones, also known as cholelithiasis, are hardened deposits of digestive fluids that develop in the gallbladder. A serious medical condition called cholelithiasis is frequently managed with general surgery. One of the treatments for cholelithiasis is an open cholecystectomy. It will take some time to recover from this surgical procedure at the hospital. The period of hospitalization will depend on the patient's weight. Numerous research findings continue to conflict with this study. As a result, this study was carried out to examine the connection between BMI and the length of hospital stay in the open cholecystectomy technique. Methods: This study used a cross-sectional study design with a sample population of cholelithiasis patients at Siloam Hospital. The sample size of 51 was selected using a purposive sampling technique. Data is taken from the patient's medical record and the data collected will be analyzed using Mann-U Whitney. Result: From 51 samples, the mean length of stay for subjects with BMI < <23 kg/ m2 was 3 days, with the lowest value being 1 day and the highest value was 5 days. Meanwhile, the mean length of stay for subjects with BMI > 23 kg/ m2 was 3 days with the lowest value was 2 days and the highest value was 6 days. From the Mann-U Whitney test, it was found that the results of the comparison were not significant (p> 0.05). Conclusions: This study shows there is no relationship between BMI and duration of hospitalization in cholelithiasis symptomatic patients undergoing open cholecystectomy surgery.